Optimization of Extraction of Natural Pigment from Purple Sweet Potato by Response Surface Methodology and Its Stability - Jinwei Li; Lianfu Zhang; Yuanfa Liu (Journal of Chemistry)
Purple sweet potato colour (PSPC) was a kind of natural pigment that attracted the general concern in recent years. In this paper, the response surface methodology was employed to optimize the extraction conditions of PSPC. The results showed that the extraction yield of purple colour was 11.6355 mg/g at the optimum extraction conditions of extraction temperature 60°C, extraction time 1 h, the ratio of solid to liquid ratio of 1 : 30, and acidified ethanol solution concentration 80%. Stability experiment showed that Fe3+ and Al3+ could increase the stability of PSPC, but Cu2+, Zn2+, and Pb2+ would decrease the stability of PSPC. Ascorbic acidified could significantly increase the stability of PSPC, and Na2SO3 would reduce the PSPC’s stability.